2021
DOI: 10.1021/acs.jafc.1c01851
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation of Black Tea Extract (BTE) with the High Content of Theaflavin Mono- and Digallates and the Protective Effects of BTE on CCl4-Induced Rat Liver and Renal Injury

Abstract: Theaflavins (TFs), formed by the dimerization of green tea catechins during “fermentation” to prepare black tea, possess antioxidant and anti-inflammatory effects. Reported efficacious effects of black tea (∼2% of TFs) or related products come from catechins unless TFs are assayed. The present study aimed to target the preparation of black tea extract (BTE) enriched with theaflavin mono- and digallates majorly from dry tea leaves in aqueous media versus traditional fermentation of fresh leaves. We further inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…[ 33 ] Studies show that the regular intake of flavonoid‐rich tea can prevent the development of liver diseases, indicating their outstanding potential in liver disease treatment. [ 14,34 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 33 ] Studies show that the regular intake of flavonoid‐rich tea can prevent the development of liver diseases, indicating their outstanding potential in liver disease treatment. [ 14,34 ]…”
Section: Discussionmentioning
confidence: 99%
“…[33] Studies show that the regular intake of flavonoid-rich tea can prevent the development of liver diseases, indicating their outstanding potential in liver disease treatment. [14,34] In the present study, we extracted VTE from dried Vine tea leaves and identified the major components of VTE by HPLC-MS/MS analysis (Figure 1). Among these components, dihydromyricetin of Ampelopsis grossedentata was found to prevent nonalcoholic fatty liver disease by improving mitochondrial respiratory capacity and redox homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al found that silymarin intervention improved liver steatosis and hepatic lobular inflammation ( 46 ). Another study found that black tea extract prevents liver fibrosis in rats by regulating the TGF-β/Smad/ERK signaling pathway ( 47 ). Thus, flavonoids have high medicinal value.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that oxidative stress and inflammatory responses are the main pathogenic factors in CCl 4 -induced liver injury [ 21 , 22 ]. In brief, when CCl 4 enters hepatocytes, it is metabolized by the cytochrome 450 enzyme family (CYP family), leading to the generation of the trichloromethyl radical (CCl 3 • ) and the trichloromethyl peroxide radical (Cl 3 COO • ).…”
Section: Discussionmentioning
confidence: 99%